AERATION AND SLOW SAND FILTRATION IN SMALL SYSTEMS - ARAL, N (MARCEL DEKKER INC, 1993)
Treatment technologies for small systems should have lower construction and operation cost, lower maintenance and labor requirements as well. The quality of groundwater in the Fezzan area of Libya for drinking purposes is not acceptable when compared to the quality of standards given by WHO. Hence, the groundwater has to be treated before being used for drinking purposes. In the Sahara Desert there is a tremendous amount of sand which is suitable for slow sand filtration and rapid sand filtration within the water treatment objectives.
Keywords: AERATION; SLOW SAND FILTRATION; SMALL TREATMENT SYSTEM; DRINKING WATER; GROUNDWATER TREATMENT; Engineering; Environmental Sciences & Ecology